Wnt5a mediates the effects of Bushen Huoxue decoction on the migration of bone marrow mesenchymal stem cells in vitro - Wei Shen; Hui Luo; Liangliang Xu; Zhifang Wu; Hongtai Chen; Yamei Liu; Lijuan Yu; Liuchao Hu; Bin Wang; Yiwen Luo (BMC, 2018)
Abstract Background Bushen Huoxue decoction (BHD) has a significant effect on fracture rehabilitation, yet its underlying mechanism is still unknown. The purpose of this study was to explore whether BHD promotes bone marrow mesenchymal stem cell (BMSC) migration through the Wnt5a signalling pathway. Methods BHD was extracted by petroleum, and its composition was analysed. Cell viability in the presence of various concentrations of BHD for 24, 48 and 72 h was measured using a Cell Counting Kit-8 assay. Transwell assays and wound healing assays were used to observe the migration ability of BMSCs. Lentiviral vectors were used to knock down Wnt5a. Polymerase chain reaction and Western blot analyses were used to further compare Wnt5a signalling components at the mRNA and protein levels between groups. Results BHD treatment groups showed increased migration ability and Wnt5a expression. Knocking down Wnt5a using a lentivirus significantly inhibited the effects of BHD, which implies that BHD promotes BMSC migration ability through activation of Wnt5a. Conclusions BHD can enhance BMSC migration, possibly by activating Wnt5a signalling.